Economical and Efficient Way of Supplying Electricity to Remote Locations - Srinivas, V.A.S.; Ramesh, D. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The model consists of hybrid wind and diesel energy conversion systems. The basic components of the wind energy conversion system are wind turbine, two mass drive train, permanent magnet synchronous generator, pitch angle controller, power converter, boost converter. The diesel energy conversion system consists of diesel engine, generator, power converter. In addition, a battery energy storage system can be connected, which provides the necessary power whenever there is a decrease in wind speed. The diesel engine is switched on basing on the requirement